Pemeliharaan Perlengkapan dan Inventaris Kantor BKDPSDM di Kota Medan - Miftah Alaina Hammi; Arnida Wahyuni Lubis (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2022)
Maintenance of equipment in the office to organize and organize to make it look good and tidy. and can be used for agency purposes. Maintain equipment every day in the office to make sure the items are in good and tidy condition. The purpose of this study is the maintenance of equipment maintenance and inventory of the BKDPPSDM office in Medan City. The data collection method used in this research is the result of field studies. Data collection techniques used in this field study method are documentation, interviews and observations. Data Analysis Methods Data analysis used was descriptive qualitative analysis method.